Sistem Moneter Islam: Menuju Kesejahteraan Hakiki - Narullah, Aan (State Institute of Islamic Studies (IAIN) Palu, 2016)
The Studies in this article aims to look at how the efforts of the Islamic monetary system in creating the true welfare. Welfare in the conventional economic system (capitalist and socialist) contain of different meanings, when in the conventional economic system, welfare is defined only in terms of materials (material fulfillment), but in the Islamic economic system, welfare contains of broader meaning, the fulfillment of material and immaterial. As Islamic monetary strategy that prohibit sto use of interest, the Islamic monetary instrument does too. The Islamic monetary policy instrument is divided into three mazhab based on the period and the community needs at that time. The first mazhab is the instrument that introduced by mazhab iqtisoduna is Promissory Notes or Bill of Exchange kind of paper to get fresh funds. The second madzhab is the mainstream instruments mazhab that used Dues of Idle Fund is policy instrument that is charged on all assets which are idle. The third mazhab is the alternative monetary system that advocated of Syuratiq Process. It is where a policy that taken by the monetary authorities is based on discussion prior with the real sector. Which is the main characteristic of the Islamic monetary system in its policy instruments are not leaving the ideology of Islamic economics nor throw needs of economic returns for economic players, namely profit sharing. Then it is expected satisfy the human need for material and immaterial, so the true welfare can be achieved